2009
DOI: 10.1007/s10534-008-9185-0
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of microbial iron assimilation processes for the development of new antibiotics and inspiration for the design of new anticancer agents

Abstract: Pathogenic microbes rapidly develop resistance to antibiotics. To keep ahead in the “microbial war”, extensive interdisciplinary research is needed. A primary cause of drug resistance is the overuse of antibiotics that can result in alteration of microbial permeability, alteration of drug target binding sites, induction of enzymes that destroy antibiotics (ie., beta-lactamase) and even induction of efflux mechanisms. A combination of chemical syntheses, microbiological and biochemical studies demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
100
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 77 publications
0
100
0
Order By: Relevance
“…The other iron-regulated protein bands Synthetic vanchrobactin and vanchrobactin analogues use FvtA as the sole route of entry. As mentioned above, the route of entry of Fe-siderophore complexes into bacterial cells can be exploited by using a Trojan horse strategy for introduction of modified molecules with antimicrobial activity (24,26). In a previous study, a series of vanchrobactin analogues were found to promote growth of V. anguillarum (RV22 and 775 strains) under iron-deficient conditions, indicating that they are indeed internalized and utilized as siderophores (37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other iron-regulated protein bands Synthetic vanchrobactin and vanchrobactin analogues use FvtA as the sole route of entry. As mentioned above, the route of entry of Fe-siderophore complexes into bacterial cells can be exploited by using a Trojan horse strategy for introduction of modified molecules with antimicrobial activity (24,26). In a previous study, a series of vanchrobactin analogues were found to promote growth of V. anguillarum (RV22 and 775 strains) under iron-deficient conditions, indicating that they are indeed internalized and utilized as siderophores (37).…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate penetration of antibiotics into bacterial cells, the so-called "Trojan horse strategy" can be employed, where antimicrobial drugs are transported across the bacterial membranes by exploiting the iron uptake pathways (7,8,24,26,34,38). The vanchrobactin chemical structure was recently determined, and a series of vanchrobactin analogues which have functionality (an amino group) appropriate for use as antibiotic vectors and keep their siderophore activity have been synthesized and evaluated (36, 37).…”
mentioning
confidence: 99%
“…At present, this approach has been utilized to design antibiotics capable of overcoming resistance due to membrane penetration by delivering the lethal moiety to the site of action [9]. For example, the conjugation of artemisinin to mycobactin siderophore yielded a compound with potent antimycobacterial activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike classical antibiotics, which target a specific reaction or process, metals and metaloorganic compounds often affect several different groups of biomolecules, and therefore, development of resistance is unlikely, which makes these compounds attractive as antibacterial agents (25,39). While classical antibiotics are less efficient against bacterial biofilms than planktonic cells, there is evidence that this is not the case for metal ions (24).…”
mentioning
confidence: 99%